Muffin Technique Micrographic Surgery for Non-melanoma Skin Cancer - Surmanowicz, Philip; Sivanand, Arunima; Du, Amy X.; Mahmood, Muhammad N.; Gniadecki, Robert (Frontiers in Medicine, 2021)
Background: Mohs micrographic surgery (MMS) is the gold standard treatment for high-risk facial non-melanoma skin cancer. However, patients’ access to MMS is limited by cost. The muffin technique micrographic surgery (MTMS) is an alternative micrographic technique wherein the entire excised margin is evaluated post-operatively by a pathologist using paraffin-embedded material. Herein, we describe the implementation and the preliminary results of MTMS in an academic dermatology center. Objective: To describe the MTMS and outline its efficacy and safety in a real-world clinical academic setting. Methods: A retrospective chart review was conducted of all patients with basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) who underwent MTMS at the University of Alberta Dermatology Center from June 2016 until July 2019. Results: A total of 69 patients were included (64 BCCs and 5 SCCs). 68.1% of surgeries had clear margins following the first incision, 100% after second round re-excisions. There were no observed cases of tumor recurrence after a median 32 months of follow-up. There were no major adverse events or complications. Conclusions: MTMS is a superior alternative to simple excision of skin cancer by providing full margin control and residual tumor mapping.